2003
DOI: 10.1007/s00535-002-1122-3
|View full text |Cite
|
Sign up to set email alerts
|

Poorly controlled ulcerative colitis treated by colectomy during remission induced by extracorporeal leukocyte removal therapy

Abstract: Both monocyte-granulocytapheresis (M-GCAP) and leukocytapheresis (LCAP) are categorized as extracorporeal leukocyte removal therapies (ECCTs). These therapies have been recognized as efficient adjuncts for patients of steroid-resistant ulcerative colitis (UC). This study aimed to consider the adaptation and the limitation of these new therapies from the clinical standpoint based on a case of UC showing strong resistance to high-dose continuous steroid injection therapy. The patient successfully underwent a sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…We hypothesized that the platelet reduction achieved during LCAP might amplify its therapeutic efficiency for UC patients with severe mucosal damage by restoring blood microcirculation in the colonic mucosa. 24 The results of the endoscopic evaluation in this study seemed to support this hypothesis, since LCAP induced a significant improvement only in the factor "mucosal damage" among EI components.…”
Section: Discussionsupporting
confidence: 62%
“…We hypothesized that the platelet reduction achieved during LCAP might amplify its therapeutic efficiency for UC patients with severe mucosal damage by restoring blood microcirculation in the colonic mucosa. 24 The results of the endoscopic evaluation in this study seemed to support this hypothesis, since LCAP induced a significant improvement only in the factor "mucosal damage" among EI components.…”
Section: Discussionsupporting
confidence: 62%
“…However, it seems to be ineffective for patients with a long disease history. 11,12 Sawada et al 13 reported that LCAP is effective and safe for treating patients with severe or fulminant UC with toxic megacolon (TM). Nevertheless, LCAP should be considered as an option only for the management of TM or a bridging therapy to surgery, thereby avoiding a high-risk emergency colectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, the mean CAI score for the LRT group (8; range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] was significantly greater than that for the without LRT group (7.5; range, 2-16). We found infectious complications in 6 (13.0%) of 46 patients in the LRT group and 10 (6.8%) of 147 in the without LRT group, a difference that was not significant.…”
Section: Postoperative Complicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent unpublished randomized controlled study comparing intensive and once a week regimen showed that intensive treatment, which consists of two aphereses in a week for 5 consecutive weeks, results in higher remission rates according to both clinical and endoscopic criteria and shorter duration before getting clinical response. Although, for steroid-resistant severe UC, intravenous infusion therapy of cyclosporine has been widely accepted as an adjunct therapy [42], a large proportion of patients may have surgery in future years. Clinical experience so far suggests that cytapheresis has superior efficiency as a non-pharmacological immunomodulative therapy for steroid-resistant UC patients before colectomy [1][2][3][4].…”
Section: Future Development In Cytapheresis For the Management Of Infmentioning
confidence: 99%